High physical activity alleviates the adverse effect of higher sedentary time on the incidence of chronic kidney disease. Issue 1 (25th December 2022) - Oh, Wonsuk; Cho, Minhae; Jung, Su Woong; Moon, Ju‐Young; Lee, Sang‐Ho; Hwang, You‐Cheol; Kim, Yang Gyun
Abstract: Background: Low physical activity (PA) increases the prevalence of chronic kidney disease (CKD). This study aimed to investigate the effects of PA and sedentary time (ST) on the changes in renal function and the development of CKD in the middle‐aged Korean population. Methods: From the Korean Genome and Epidemiology Study Database, 7988 participants in their 40s and 60s were identified and stratified by (1) PA: high‐PA (>24 MET‐h/day), moderate‐PA (9–24 MET‐h/day) and low‐PA (<9 MET‐h/day); and (2) ST: high‐ST (>6 h/day), moderate‐ST (3–6 h/day) and low‐ST (<3 h/day). Incident CKD was defined as estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m 2 following the Chronic Kidney Disease Epidemiology Collaboration equation. Results: The mean age of the participants was 52.0 years. The overall incidence of CKD was 16.8 per 1000 person‐years over a median of 12 years. The lower the PA and the higher the ST, the lower the baseline eGFR. Relative to the high‐PA, the coefficients of the annual eGFR decline were −0.12 (95% confidence interval [CI]: −0.26 to 0.001, P  = 0.081) and −0.13 (95% CI: −0.27 to 0.01, P  = 0.078) in the moderate‐ and low‐PA groups, respectively. Similarly, relative to the low‐ST, the coefficients of annual eGFR decline were −0.07 (59% CI: −0.19 to 0.05, P  = 0.236) and −0.14 (95% CI: −0.28 to −0.01, P  = 0.039) in the moderate‐ and high‐ST groups, respectively. Incident CKD was higher with lower PA (hazard ratio: high‐PA 1.00, moderate‐PA 1.13 [1.00, 1.28, P  = 0.056] and low‐PA 1.25 [1.11, 1.24, P  < 0.001]) and higher ST (hazard ratio: low‐ST 1.00, moderate‐ST 1.04 [0.94, 1.16, P  = 0.440] and high‐ST 1.19 [1.05, 1.34, P  = 0.007]). The high‐PA reduced the risk for the CKD development irrespective of the amount of ST. Conclusions: Low‐PA and high‐ST are risk factors for the development of CKD in the middle‐aged Korean population. High‐PA recovers high‐ST, inducing a harmful effect on the occurrence of CKD.